Brand recall as indication of television advertising effectiveness - Mohd Miharbi, Maldia Syela (2001)
With the increase of the business world's competition, advertisements become a major tool for marketing strategies. Thus, the effectiveness of television advertisements to generate and register brand into consumers' mentality is becoming a main concern for the marketers. Advertising is an important social phenomenon that stimulates purchasing power and economic activities that is being influenced by certain value of adaptation and life-styles. Everyone seems to hold an opinion about various aspects of advertisement, ranging from the informative, amusement to the hostility brought to the viewers. This study intends to find out what factors that may affect the brand recall score and to investigate the ability of television advertisement to generate brand recall. Factors such as consumers' attitude, feeling, familiarity towards the advertisement and elements of attractiveness were considered. A model adopted from Meryl Paula Gardner (1983), and Julie A. Edell and Marian Chapman Burke (1987) has been modified to assess the ability of brand recall using advertisement that will provide guidelines on how to maximize its effectiveness. The findings showed that the Malaysian consumers still hold positive attitude towards advertisement and are more likely to brand recall. Generally, the research has the evidence that consumer demographic characteristics have the positive relationship with the ability of brand recall. This study suggests that consumer's attitude, feeling (experience/knowledge) and elements of attractiveness are the factors to illustrate the effectiveness of television advertising in generating brand recall. However, the data, which has been collected from the research, contradicts with the model used. Familiarity, as on of the variables shows no significant relationship with the brand recall due to culture and lifestyle factors.